2016
DOI: 10.1038/ncomms10907
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-mediated crowd control in an active matter system

Abstract: Living active matter systems such as bacterial colonies, schools of fish and human crowds, display a wealth of emerging collective and dynamic behaviours as a result of far-from-equilibrium interactions. The dynamics of these systems are better understood and controlled considering their interaction with the environment, which for realistic systems is often highly heterogeneous and disordered. Here, we demonstrate that the presence of spatial disorder can alter the long-term dynamics in a colloidal active matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 32 publications
(58 reference statements)
1
77
0
Order By: Relevance
“…Theoretical studies have shown that the existence of spatial light chaos will greatly affect the movement of active matters. Pince et al [52] studied the aggregation and dispersion behavior of colloidal particles in hot baths and active bacterial fluids when controllable roughness of the spatial light is introduced by optical potential well. They found that the existence of spatial chaos controlled by external field did change the long-range coupling behavior of the active system.…”
Section: Collective Behavior Of Bacteria In Confined Spacementioning
confidence: 99%
“…Theoretical studies have shown that the existence of spatial light chaos will greatly affect the movement of active matters. Pince et al [52] studied the aggregation and dispersion behavior of colloidal particles in hot baths and active bacterial fluids when controllable roughness of the spatial light is introduced by optical potential well. They found that the existence of spatial chaos controlled by external field did change the long-range coupling behavior of the active system.…”
Section: Collective Behavior Of Bacteria In Confined Spacementioning
confidence: 99%
“…

We report an autonomous oscillatory micromotor system in which active colloidal particles form clusters,the size of whichc hanges periodically.T he system consists of an aqueous suspension of silver orthophosphate microparticles under UV illumination, in the presence of varying concentrations of hydrogen peroxide.The colloid particles first attract each other to form clusters.A fter as hort delay,t hese clusters abruptly disperse and oscillation begins,a lternating between clustering and dispersion of particles.After acluster oscillation initiates,the oscillatory wave propagates to nearby clusters and eventually all the clusters oscillate in phase-shifted synchrony. [4][5][6][7][8][9] These synthetic collective systems,when combined with other biomimetic functions,c ould lead to advances in chemical sensing, signal processing, drug delivery,and environmental remediation. The addition of inert silica particles to the system results in hierarchical sorting and packing of clusters.D ensely packed Ag 3 PO 4 particles form an on-oscillating core with an oscillating shell composed largely of silica microparticles.

Self-organization takes the form of dynamic patterning and structures in living systems over arange of length scales,from fish schools to bacteria colonies and structural protein assemblies.

…”
mentioning
confidence: 99%
“…We underline that this transition from a situation that can be described with Boltzmann statistics, albeit at a higher effective temperature, and a situation that cannot be described by Boltzmann statistics associated with the ratio between the characteristic scales of the trapping potential and the correlated active noise underlies several results connected with broken symmetries in active matter [34,35,41,[44][45][46][47].…”
Section: -3mentioning
confidence: 84%
“…We realize the active bath by adding motile bacteria to the watery solution where the particle is immersed [33,34] [inset in Fig. 2(a)]: The bacteria behave as active particles and exert nonthermal forces on our probe particle so that it experiences nonthermal fluctuations and features a qualitatively different behavior from that of a Brownian particle in a thermal bath.…”
Section: Langevin Equationmentioning
confidence: 99%